Birds of a Caste - How Caste Hierarchies Manifest in Retweet Behavior of Indian Politicians - Vaghela, Palashi; Mothilal, Ramaravind K; Pal, Joyojeet (2021)
The Hindu caste system plays an important role in the socio-political landscape of India. In recent years, Indian politicians have moved a lot of direct communication online. Social media is now an important space for the articulation and performance of their political positions. In this paper, we study ways in which the political performance of caste relations can be captured from the online connections and messaging of parliamentarians in India. We run tests of odds ratios among the members of Lok Sabha (lower house) of India to find the extent to which their engagement is insular to their own caste group versus other groups. We observe that in the Lok Sabha network, Members of Parliament (MPs) have higher odds of getting retweeted by others whose caste is the same or closer to their own in the caste hierarchy. The findings of this research shed light on an understudied, yet critical, social relation of caste in the study of political behavior on social media.